On the Ideal Convergence of Double Sequences in Locally Solid Riesz Spaces. (2nd April 2014) - Alotaibi, A.; Hazarika, B.; Mohiuddine, S. A.
Abstract : The aim of this paper is to define the notions of ideal convergence, I -bounded for double sequences in setting of locally solid Riesz spaces and study some results related to these notions. We also define the notion of I * -convergence for double sequences in locally solid Riesz spaces and establish its relationship with ideal convergence.